Efficacy and risk factors of stent placement in the treatment of malignant tracheoesophageal fistula - Wang, Qingxia; Duan, Zhihong; Liu, Shiqi; Shi, Ruihua (Frontiers in Oncology, 2024)
Background Due to the low incidence of malignant tracheoesophageal fistula and the paucity of relevant clinical studies, the benefits of stent implantation have not been well documented. It remains unclear which factors may affect fistula closure. Methods Between January 2015 and January 2021, 344 patients who were diagnosed with malignant tracheoesophageal fistula at Zhongda Hospital, Southeast University, were retrospectively enrolled. Demographic and clinical data were collected. Risk factors for fistula closure identified by univariate analysis were further analyzed using multivariable logistic regression. Results A total of 288 patients were analyzed in this study, of which 94 were treated conservatively, 170 were treated with an esophageal stent, and 24 were treated with a tracheal stent. Among them, the delta Karnofsky’s performance status score values (after 2 weeks/before treatment [p = 0.0028], after 1 month/before treatment [p = 0.0103]) were significantly different between conservative and stent treatment. There was a significant reduction of pneumonia incidence in the stenting group (33.53%) compared to the conservative treatment group (77.05%) after one month (p <0.0001). In addition, the closure of fistulas was influenced by four independent risk factors: 1) treatment methods (p < 0.0001), 2) fistula size (p = 0.0003), 3) preoperative white blood cell count (p = 0.0042), and 4) preoperative Karnofsky’s performance status score (p = 0.0001). Conclusions Stent implantation has become an effective method for treating malignant tracheoesophageal fistula compared to conservative treatment. Additionally, stent implantation, smaller fistula size, lower preoperative white blood cell count, and higher preoperative Karnofsky’s performance status score suggest a better outcome.